PERBANDINGAN HASIL BELAJAR KOGNITIF MODEL PBL DENGAN GI DENGAN MEMPERTIMBANGKAN BENTUK SOAL - Suryo Pranoto; Edy Purnomo; Yon Rizal (FKIP Unila, 2015)
This research was based on the low learning outcomes and the lack of students in the learning activity of IPS. Population of 81 students using cluster random sampling technique obtained a sample of 54 students. 2 x 2 factorial method was used in this research. The purpose of the study was to find out the results of the comparison of the cognitive learning result of Problem Based Learning model with the Group Investigation cooperative model by considering the question form. The results of the analysis of the data showed that there is a comparison of the Learning results using Problem Based Learning with the Group Investigation cooperative model by considering the question form.Penelitian ini dilatar belakangi oleh rendahnya hasil belajar dan kurangnya aktivitas siswa di dalam pembelajaran IPS. Populasi berjumlah 81 siswa dengan menggunakan tekhnik cluster random sampling didapat sampel 54 siswa. Metode yang digunakan factorial 2x2. Tujuan penelitian untuk mengetahui perbandingan hasil belajar kognitif model Pembelajaran Berbasis Masalah dengan Model Kooperatif Group Investigasi dengan mempertimbangkan bentuk soal. Hasil analisis data menunjukkan Ada Perbandingan Hasil Belajar Kogniktif menggunakan Model Pembelajaran Berbasis Masalah dengan Model Kooperatif Group Investigasi dengan mempertimbangkan bentuk soal.Kata kunci : bentuk tes, GI, hasil belajar, PBL